DESIGN OF A POPULATION ADMINISTRATION SERVICE INFORMATION SYSTEM IN SADENG VILLAGE, BOGOR REGENCY - Rachmat Suryadithia; Ananda Sandi Wildani Sabihis; Witriana Endah Pangesti; Muhammad Faisal (INFOKUM, 2022)
The village is the smallest unit of government legally recognized by the Indonesian government. One of the tasks of the village administration is to provide administrative services to its inhabitants. Preparation of population documents such as identity, cards or residence documents that are subject to change must be considered carefully in the registration process for population data. The technology in the web-based population administration service system is a breakthrough in the context of increasing community satisfaction with village government performance as well as optimizing technology in the field of information and communication whereby using this technology the public can be served anytime and anywhere. The Sadeng Village Office, Bogor Regency, is the institution that exercises authority in the field of population administration in Sadeng Village. In organizing activities in Sadeng Village, problems often occur in the process of recording population administration, one of which is the delay in the recording process which still uses a manual system, namely by writing all submissions using paper. by using the waterfall method or linear sequential or classical life flow it is hoped that it can help the community in the submission process, as well as make it easier for village officials to collect population data. With the design of this information system, it is hoped that data management in the village will become more effective and efficient..